EVALUATION OF SULFURIC ACID, BARIUM CHLORIDE, AND SEED GERMINATION ASSAY METHODS AS EARLY PREGNANCY DETECTION INSTRUMENTS IN CATTLE - Zul Azmi; Muhammad I. Desem; Hastuti Handayani S. Purba; Dwi Endrawati; Faidah Rachmawati; Eni Kusumaningtyas; Didik T. Subekti (Universitas Syiah Kuala, 2020)
This study aims to validate and re-evaluate the use of H2SO4, BaCl2, and seed germination assay (SGA) methods to detect early pregnancy in cattle. Validation was carried out in order to find out the actual test performance value, which include accuracy, sensitivity, and specificity.Validation test was done by reacting the urine of pregnant and non-pregnant cattle populations with H2SO4 solution diluted at a ratio of 1 : 4, with 1% BaCl2 solution or through germination of mung bean seeds in Petri dishes. The results of this study indicated that the H2SO4 and BaCl2 methods have poor accuracy (21.88% and 28.13%) with the sensitivity of 81.82% and 100% and specificity of 9.43% and 13.21%, respectively. Meanwhile, the SGA method had a fairly good accuracy (74.55%) with sensitivity and specificity of 45.46% and 81.82%, respectively. Based on these results, the H2SO4, BaCl2, and SGA methods are not recommended for detection of early pregnancy in the field.